Megarthrus of China. Part 5. The M. calcaratus complex, with description of three new species (Coleoptera: Staphylinidae: Proteininae) - Liu, Zhiping; Cuccodoro, Giulio (Zootaxa, 2021)
Three new species of Megarthrus Curtis from mainland China belonging to the M. calcaratus species complex are described: M. bajie Liu & Cuccodoro sp. nov., M. wujing Liu & Cuccodoro sp. nov., and M. wukong Liu & Cuccodoro sp. nov.. Also pertaining to this lineage of Megarthus, the East Palaearctic M. zerchei Cuccodoro & Löbl is reported here to occur in China (new country record). These four species are diagnosed, illustrated, and keyed. Their distribution in mainland China is mapped, and their affinities are briefly discussed.